2022
DOI: 10.1111/ina.12983
|View full text |Cite
|
Sign up to set email alerts
|

Human exposure to aerosol from indoor gas stove cooking and the resulting nervous system responses

Abstract: Our knowledge of the effects of exposure to indoor ultrafine particles (sub‐100 nm, #/cm3) on human brain activity is very limited. The effects of cooking ultrafine particles (UFP) on healthy adults were assessed using an electroencephalograph (EEGs) for brain response. Peak ultrafine particle concentrations were approximately 3 × 105 particle/cm3, and the average level was 1.64 × 105 particle/cm3. The average particle number emission rate (S) and the average number decay rate (a+k) for chicken frying in brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…With respect to particle total number emission rates, the oils were ranked as olive > coconut > corn > soybean, canola > safflower > peanut. Olive, coconut, corn, and peanut oils generated higher total particle number than safflower, soybean, and canola oils at 197°C 152,155,156 …”
Section: Cookingmentioning
confidence: 95%
See 2 more Smart Citations
“…With respect to particle total number emission rates, the oils were ranked as olive > coconut > corn > soybean, canola > safflower > peanut. Olive, coconut, corn, and peanut oils generated higher total particle number than safflower, soybean, and canola oils at 197°C 152,155,156 …”
Section: Cookingmentioning
confidence: 95%
“…Olive, coconut, corn, and peanut oils generated higher total particle number than safflower, soybean, and canola oils at 197°C. 152,155,156 Evidence from many studies has shown that cooking on a gas stove produces in general a higher level of UFPs, PM, and NOx than electric-stove cooking. 131,151,156,157 Cooking appliance type is another factor in aerosol formation during the cooking process.…”
Section: Cookingmentioning
confidence: 99%
See 1 more Smart Citation
“…With high time sensitivity, EEG can record electrical activity with synchronized task 28 . At present, the EEG method has been widely utilized to better understand cognitive activity, which proved to be a sensitive measure of assessing the impact of air pollutant on human brain 29–31 …”
Section: Introductionmentioning
confidence: 99%
“…28 At present, the EEG method has been widely utilized to better understand cognitive activity, which proved to be a sensitive measure of assessing the impact of air pollutant on human brain. [29][30][31] Attention is the precondition of advanced cognitive functions composed of three functionally and anatomically distinct subsystems known as alerting network, orienting network, and executive network (EC). 32,33 The attention network test (ANT) designed by Fan et al was used to evaluate the efficiency of three components of attention network, 34 and distinct brain oscillation pattern of the attention network has been found in previous research.…”
Section: Introductionmentioning
confidence: 99%